(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
The growing scarcity of fresh water source is driving the implementation of desalination on an increasingly large scale. The idea of using renewable energy source is fundamentally attractive and many studies have been conducted in this area. Solar distillation is one of the promising effect that uses solar radiation effectively to produce fresh water. Since there are various methods of solar distillation depending upon various factors, the number of slopes of glazing cover is one of the key factor. This paper presents a theoretical and experimental work performed on a double slope and multi sloped (four) solar still. In this work, additional slopes is incorporated with conventional double slope still to analyze the performance. Double and four sloped solar stills are fabricated with the area of 1.4 m2 and would be tested under same operating parameters and same climatic conditions. In these experiments the fresh water productivity is 3.9 liters for multi sloped still with 29.5% efficiency while for double slope the productivity is 3.1 litres with efficiency of 25.08%. The results indicates that the productivity and efficiency of fresh water will increase for more slopes up to certain limit.